Unmasking the mimic: lipoid pneumonia imitating primary lung cancer - a case report series of a diagnostic challenge - Mohamed, Shehab; Bertolaccini, Luca; Lombardi, Mariano; Di Tonno, Clementina; Sabalic, Angela; Casiraghi, Monica; Spaggiari, Lorenzo (Frontiers in Oncology, 2025)
IntroductionLipoid pneumonia is a rare inflammatory disease characterized by an abnormal deposition of lipids in the alveoli. It may manifest as pulmonary consolidation, simulating primary lung cancer on radiological imaging and an increased uptake on fluorine-18-fluorodeoxy-D-glucose (FDG) positron-emission tomography (PET)/computed tomography (CT). The confirmed diagnosis can be achieved only by microscopic examination of cytological or histological samples.MethodsThis paper describes eight cases at a single center from 2016 to 2024 of lipoid pneumonia mimicking primary lung cancer and its risk factors. Samples were collected thanks to multidisciplinary evaluations using CT and FDG-PET/CT. The histopathological diagnoses were obtained with endobronchial ultrasound (EBUS), fine needle aspiration biopsy (FNAB), or, as a last resort, surgical resection.ResultsOur cohort of patients confirms that lung masses with fat density and irregular margins are lipoid pneumonia’s most common findings. However, it can also present as a solid mass with no fat density. This condition must always be appropriately evaluated through a multidisciplinary approach, especially when excluding a neoplastic origin.ConclusionIn this paper, we present the largest case series of lipoid pneumonia mimicking primary lung cancer from a single center reported in the literature so far. This case series highlighted the critical role of a multidisciplinary approach, including radiologists and pathologists, in differentiating lipoid pneumonia from malignancy to ensure optimal patient management.